2013
DOI: 10.1016/j.ijgo.2013.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Outreach and integration programs to promote family planning in the extended postpartum period

Abstract: Background WHO recommends birth spacing to improve the health of the mother and child. One strategy to facilitate birth spacing is to improve the use of family planning during the first year postpartum. Objectives To determine from the literature the effectiveness of postpartum family-planning programs and to identify research gaps. Search strategy PubMed and the Cochrane Central Register of Controlled Trials were systematically searched for articles published between database inception and March 2013. Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…The rationale for our trial approach is based on WHO's seminal 2013 publication of programmatic strategies for post-partum family planning 2 and three other systematic reviews (without meta-analysis) on post-partum family planning interventions in low-income and middle-income countries published between 2014 and 2016. [6][7][8] These publications suggest that the following interventions could have a positive effect on post-partum contraceptive uptake: counselling activities during antenatal care; provision of post-partum family planning information, education, and counselling materials before women are discharged from health facilities after birth, including provision of emergency contraception for women using the lactational amenorrhoea method; promotion by community-based counsellors of exclusive breastfeeding practices before 5−6 months post partum; access to contraceptive methods immediately after birth, including intrauterine devices; provider competencies in quality counselling and the provision of quality services with several readily available products; and long programmes with several contact points between providers and clients across the continuum of care versus short antenatal interventions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for our trial approach is based on WHO's seminal 2013 publication of programmatic strategies for post-partum family planning 2 and three other systematic reviews (without meta-analysis) on post-partum family planning interventions in low-income and middle-income countries published between 2014 and 2016. [6][7][8] These publications suggest that the following interventions could have a positive effect on post-partum contraceptive uptake: counselling activities during antenatal care; provision of post-partum family planning information, education, and counselling materials before women are discharged from health facilities after birth, including provision of emergency contraception for women using the lactational amenorrhoea method; promotion by community-based counsellors of exclusive breastfeeding practices before 5−6 months post partum; access to contraceptive methods immediately after birth, including intrauterine devices; provider competencies in quality counselling and the provision of quality services with several readily available products; and long programmes with several contact points between providers and clients across the continuum of care versus short antenatal interventions.…”
Section: Methodsmentioning
confidence: 99%
“…5 According to various literature reviews, the evidence is often weak or incomplete in terms of research design and quality, details about the interventions, or women's pers pectives. [6][7][8] There is also a paucity of studies looking at operationally feasible ways to integrate post-partum family planning into existing antenatal and postnatal care, for example through meaningful involvement of community actors. 2 In response, the Yam Daabo trial (meaning "your choice" in Mooré, one of the local languages in Burkina Faso) was designed to test the effectiveness of a low-technology, postpartum family planning intervention package, established using participatory action research, on contraceptive uptake.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of outreach and integration programs to promote postpartum contraception identified 34 publications, of which about half related to developing countries and seven were additional to those included in the Cochrane reviews (Sonalkar, Mody, and Gaffield 2014). An earlier review of family planning integration with other health services described four studies related to postpartum contraception, two of which were not included in the 2014 review by Sonalkar and colleagues (Kuhlmann, Gavin, and Galavotti 2010).…”
Section: December 2015mentioning
confidence: 99%
“…The expert group of 180 stakeholders identified PPFP service integration mechanisms and the development of effective strategies to overcome barriers to contraceptive uptake during the postpartum period as the second and fourth highest research priorities among a list of 47 topics. A new review of 34 PPFP programs confirms the difficulty of assessing program effectiveness without rigorous research designs and outlines the plethora of PPFP interventions that have not been studied systematically 15 . There is an urgent need to scientifically investigate why certain PPFP interventions work—and why others do not—and why some integration opportunities that seem obviously beneficial, such as those at immunization visits, have shown weaker results than expected.…”
Section: Time For Action On Ppfpmentioning
confidence: 99%